Technology applied to optimise training for improvement of front-crawl swimming performance - Toussaint, H. M. (Biomechanics and Medicine in Swimming X, 2006)
Peak performances in swimming require the full deployment of all powers a swimmer possesses. The development of those powers require years of hard training. Developments of measurement technology (e.g. MAD-system (16)) have aided the sport scientist in identifying several factors as determinants of performance. These include drag, propulsion technique, and mechanical power (20) . The development of this knowledge provides the modern swimming coach with some guide-lines how to design training programmes. However, it may be argued that training-time will be especially efficient when devoted to the enhancement of those performance factors that are weak links in the individual performance chain. This implies that on an individual level it is necessary to identify in what phase of the process the performance System first becomes insufficient. In the training process it is rather challenging for coaches to determine which training load is sufficient to induce the required adaptation without risk of overtraining. More insight in the individual relation between training dose and adaptation response is necessary to optimise this training process. Training dose and changes in swim performance capacity can be modelled (2). In this model performance is a Systems Output varying over time according to the Systems input; the training dose or training Impulse (TRIMP), quantified from exercise intensity and volume. Thus the swimmer is represented by a System with a daily amount of training as input and performance capacity as Output. It is possible to use heart rate recordings as training dose indicator while simple time trials monitor performance capacity development. A sketch will be given how technological developments leading to instrumented swimming wear could be put to use to optimise the training process.